Comparative Study of Various Pharmacological Screening of Argyreia Speciosa Sweet. In Relation with Ayurvedic Documented Literature - Unadkat, K P; Jani, D k; Pandey, R C (Asian Journal of Pharmaceutical Research and Development, 2019)
Vruddhadaru is one of the important herbs in Ayurveda. It has been used in Ayurvedic traditional literature for various diseases and improves the health. It is also used as folklore medicine. Out of its entire therapeutic spectrum, the herb is famous for its wound healing activity for longer time. The Latin name of Vruddhadaru is Argyreia speciosa(Syn.-Argyreia nervosa; Family-Convolvulaceae).Argyreia speciosa is commonly known as Vruddhadaru in Sanskrit, Vidhara in Hindi, Elephant creeper in English and Samudrashosha in Gujarati. It has many synonyms like Aavegi, Chhagalantri, Vrushyagandhika etc. It has been described in Dhanvantari Nighantu, Madanpala Nighantu, Kaiyadeva Nighantu, Raj Nighantu, Bhavaprakasha Nighantu, Nighantu Adarsh etc. This shows the importance of the drug. It is usually appreciated for its aesthetic merit. Therapeutically proven activities of this plant are – analgesic & anti-inflammatory, anti-cancer, anti-convulsant, anti-diarrheal, anti-fungal, anti-microbial, anti-obesity, antipyretic, anti-stress, anti-ulcer, anti-viral, aphrodisiac, CNS effect, hepatoprotective, hypoglycaemic, immunomodulatory, nootropic, wound healing activity etc. It is very interesting to observe that most of the pharmacological screened activities are documented in Ayurveda by various authors but in the language of Ayurveda. It shows that the former scientists (Ayurveda Philosophers) are extreme aware about the activity of the herb and was in practice as an Ayurveda medicine. The conventional evidences about the activity are the proof that there must be a scientific technique with the traditional healers to document the properties of the herb. The present review explains the correlation of the same activity noted by two different streams. This review helps to design futuristic pathway for pharmacological testing of herbs. Keywords: Vruddhadaaru, Argyreia speciosa, pharmacological screening, Ayurveda